Associations between phytohormones and cellulose biosynthesis in land plants. (3rd July 2020) - Wang, Liu; Hart, Bret E; Khan, Ghazanfar Abbas; Cruz, Edward R; Persson, Staffan; Wallace, Ian S
Abstract: Background: Phytohormones are small molecules that regulate virtually every aspect of plant growth and development, from basic cellular processes, such as cell expansion and division, to whole plant environmental responses. While the phytohormone levels and distribution thus tell the plant how to adjust itself, the corresponding growth alterations are actuated by cell wall modification/synthesis and internal turgor. Plant cell walls are complex polysaccharide-rich extracellular matrixes that surround all plant cells. Among the cell wall components, cellulose is typically the major polysaccharide, and is the load-bearing structure of the walls. Hence, the cell wall distribution of cellulose, which is synthesized by large Cellulose Synthase protein complexes at the cell surface, directs plant growth. Scope: Here, we review the relationships between key phytohormone classes and cellulose deposition in plant systems. We present the core signalling pathways associated with each phytohormone and discuss the current understanding of how these signalling pathways impact cellulose biosynthesis with a particular focus on transcriptional and post-translational regulation. Because cortical microtubules underlying the plasma membrane significantly impact the trajectories of Cellulose Synthase Complexes, we also discuss the current understanding of how phytohormone signalling impacts the cortical microtubule array. Conclusion: Given the importance of cellulose deposition and phytohormone signalling in plant growth and development, one would expect that there is substantial cross-talk between these processes; however, mechanisms for many of these relationships remain unclear and should be considered as the target of future studies.